THE EFFECTIVENESS OF AMAL-I-KAYY (CAUTERIZATION) IN TREATING HEEL PAIN: A CASE STUDY - Rayees Ahmad Mir; Dwarakeesha Chatrappa; Naveen Kumar M R; Mohd Nayab; Abdul Nasir Ansari (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Plantar heel pain affects over two million individuals annually, with mechanical etiologies being the most prevalent. Among these, calcaneal spurs are common, causing significant discomfort yet often resistant to conventional treatments. This case report explores the effectiveness of the Unani medicine technique, Amal-i-kayy (cauterization), in alleviating heel pain associated with a calcaneal spur. We presented a case study of a 42-year-old male patient with a one-year history of right heel pain. The patient was evaluated at the National Institute of Unani Medicine Hospital in Bangalore.The patient underwent a thorough clinical examination and imaging, confirming the diagnosis of a calcaneal spur. The intervention involved three sessions of Amal-i-kayy, performed weekly, with follow-up assessments conducted on the 0th, 7th, 14th, 21st, and 35th days post-treatment.Baseline pain assessment (VAS score of 8) improved significantly following the intervention, with scores decreasing to 4, 2, and finally 0 by the 35th day. Tenderness grading also improved, moving from severe (grade 3) to no tenderness (grade 0). The findings suggest that Amal-i-kayy not only provides immediate pain relief but may also address underlying causes of heel pain, leading to long-lasting results. Given its cost-effectiveness and simplicity, this traditional treatment warrants further investigation through randomized controlled trials to better understand its mechanisms and broader applicability.